Is netrin-1 a reliable inflammatory marker for periodontitis? - Sarah Yasser Abdulfattah; Azza Abdel Baky Baiomy; Jilan Mohammed Youssef (Tabriz University of Medical Sciences, 2022)
Background. The current study tested netrin-1 as a reliable inflammatory marker of periodontal disease. Methods. Gingival crevicular fluid (GCF) samples were taken at baseline from 30 systemically healthy individuals. Fifteen subjects had stage II grade A or B periodontitis, and 15 were periodontally and clinically healthy. Whole-mouth periodontal parameters [probing depth (PD), clinical attachment loss (CAL), plaque index (PI), and gingival index (GI)] were recorded. The GCF samples were re-collected, and clinical parameters were re-recorded after six weeks following full-mouth scaling and root planing (SRP) in the periodontitis group. Results. Netrin-1 GCF levels were significantly lower in periodontitis patients than periodontally healthy individuals at baseline with a significant increase in netrin-1 GCF levels after SRP (P<0.05). Conclusion. Netrin-1 may have a significant role in the inflammatory process of chronic periodontitis; thus, it could be a promising anti-inflammatory marker in periodontal disease.